Producción de anticuerpos monoclonales en células dendríticas de Mono Aotus spp. (2023)
Malaria is one of the tropical diseases of greatest concern due to its high rate of contagion, mainly in populations in developing countries, it is transmitted by the vector Anopheles spp. and is caused by the parasite Plasmodium spp. among the treatments that have been developed to cure and prevent this disease have not been efficient, so the search for a treatment is of great interest.